Role of Leadership in Enhancing Employee Performance in the Digital Era - Fitriana, Allysha Syatifa; Azita, Nurul; Lim, Linda (SABA JAYA PUBLISHER, 2024)
In the digital era, leadership's pivotal role in improving employee performance is Technology's transformative impact on organizations highlights the importance of effective leadership, which necessitates a profound grasp of the digital landscape to enhance workforce engagement and productivity. This abstract delves into the significance of leadership in maximizing employee performance amidst digital disruptions. In today's era, leadership extends beyond traditional management, demanding proficiency in digital tools, fostering innovation, and enabling continuous learning. Digital leaders play a crucial role in steering organizational change by embracing technology and aligning with strategic objectives, empowering employees through digital literacy and adaptability. Effective digital leadership creates collaborative environments where open communication and mentorship inspire commitment and purpose. Additionally, digital leaders leverage data-driven insights to optimize workflows and promote diversity for innovation. In conclusion, leadership's role in driving employee performance in the digital age requires visionary leadership, technological proficiency, and a human-centric approach. As organizations navigate digital challenges, effective leadership remains essential for unlocking workforce potential and ensuring sustainable growth.